PELAKSANAAN MANAJEMEN DALAM PEMBELAJARAN AKIDAH AKHLAK (STUDI KASUS DI MTsN SAMUDERA ACEH UTARA) - Wahyuni, Suci (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2021)
This research is conducted to find out how about the planning, implementation and evaluation in the learning moral aqidah at MTsN Samudera North Aceh. This research is a field study with a qualitative descriptive approach. Sources of research consist of primary and secondary data. The researcher was collected the data by using observation, interview and documentation. Data analysis is done by reducing data, presenting data and drawing conclusion on the data that has been collected. While to guarantee the validity of the data, triangulation techniques are used. The results of this study indicated that: First, Planning in the learning of moral aqidah consists of the preparation of steps in learning such as the preparations of lesson plans, syilabus, prota and prosem. Second, the implementation in learning of aqidah morality includes preliminary activities, core activities and ends with closing activities. Third, the evaluasion used in the study of moral aqidah learning includes written tests and non written tests.